2014
DOI: 10.1521/ijct.2014.7.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Choice Blindness, Confabulatory Introspection, and Obsessive-Compulsive Symptoms: A New Area of Investigation

Abstract: The current study is the first to investigate confabulatory introspection in relation to clinical psychological symptoms utilizing the Choice Blindness Paradigm (CBP). It was hypothesized that those with obsessive-compulsive symptoms are more likely to confabulate mental states. To test this hypothesis, an experimental choice blindness task was administered in two nonclinical samples (n = 47; n = 76). Results showed that a confabulatory introspection is significantly related to obsessive-compulsive symptoms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Specifically, the high-OCD group justified choices they did not actually make with more certainty in their language compared to the low-OCD group, but did not differ in how detailed and emotional their language was. As inductive narratives justifying imagined choices on manipulated trials were likened to the OCD narrative individuals with OCD use to justify an imagined state of affairs about reality (Aardema et al, 2014), our findings were somewhat consistent with what the IBA model would predict (Julien et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Specifically, the high-OCD group justified choices they did not actually make with more certainty in their language compared to the low-OCD group, but did not differ in how detailed and emotional their language was. As inductive narratives justifying imagined choices on manipulated trials were likened to the OCD narrative individuals with OCD use to justify an imagined state of affairs about reality (Aardema et al, 2014), our findings were somewhat consistent with what the IBA model would predict (Julien et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
“…Using a pencil and paper version of the CBP, Aardema et al (2014) found that those who confabulated on this task (i.e., failed to notice that their initial choice was swapped out) scored significantly higher on the obsessions subscale of the Vancouver Obsessional Compulsive Inventory than those who did not confabulate. This result could not be explained by participants wanting to present themselves favorably to the experimenter (i.e., social desirability).…”
mentioning
confidence: 98%
See 3 more Smart Citations